penelitian pendidikan Dampak Sosial Makan Bergizi Gratis (MBG) pada Lingkungan Sekolah di Kabupaten Pati - Fashihullisan, Muhammad; Aprilya, Caraka Yoga (LPPM Press, 2025)
This study aims to analyze the implementation and social impact of the free nutritious meal program in schools. The social impact of the government's implementation of the free nutritious meal program will undoubtedly affect students, teachers, educational staff, and the school environment, such as the canteen and surrounding food vendors. The method used in this study was a qualitative descriptive case study approach in an Early Childhood Education (PAUD) school and one Islamic Senior High School (MA). The study showed that the implementation of the free nutritious meal program was quite effective in Madrasah Aliyah (MA) but less effective in Early Childhood Education (PAUD). A key finding was that the free nutritious meal program had an impact on changing the relationship between the Madrasah Aliyah school and the surrounding community, particularly the canteen and food vendors. However, it had little impact on the Early Childhood Education school and its surrounding environment. The study concluded that the free nutritious meal program triggered conflict between the school and the canteen and surrounding food vendors, while it had no impact on the Early Childhood Education school.